Stress reactivity as a putative mechanism linking childhood trauma with clinical outcomes in individuals at ultra-high-risk for psychosis: Findings from the EU-GEI High Risk Study. (28th May 2021) - Paetzold, I.; Myin-Germeys, I.; Schick, A.; Nelson, B.; Velthorst, E.; Schirmbeck, F.; van Os, J.; Morgan, C.; Hartmann, J.; van der Gaag, M.; de Haan, L.; Valmaggia, L.; et al.
Abstract: Aims: Childhood trauma is associated with an elevated risk for psychosis, but the psychological mechanisms involved remain largely unclear. This study aimed to investigate emotional and psychotic stress reactivity in daily life as a putative mechanism linking childhood trauma and clinical outcomes in individuals at ultra-high-risk (UHR) for psychosis. Methods: Experience sampling methodology was used to measure momentary stress, affect and psychotic experiences in the daily life of N = 79 UHR individuals in the EU-GEI High Risk Study. The Childhood Trauma Questionnaire was used to assess self-reported childhood trauma. Clinical outcomes were assessed at baseline, 1- and 2-year follow-up. Results: The association of stress with positive ( β = −0.14, p = 0.010) and negative affect ( β = 0.11, p = 0.020) was modified by transition status such that stress reactivity was greater in individuals who transitioned to psychosis. Moreover, the association of stress with negative affect ( β = 0.06, p = 0.019) and psychotic experiences ( β = 0.05, p = 0.037) was greater in individuals exposed to high v . low levels of childhood trauma. We also found evidence that decreased positive affect in response to stress was associated with reduced functioning at 1-year follow-up ( B = 6.29, p = 0.034). In addition, there was evidence that the association of childhood trauma with poor functional outcomes was mediated by stress reactivity (e.g. indirect effect: B = −2.13, p = 0.026), but no evidence that stress reactivity mediated the association between childhood trauma and transition (e.g. indirect effect: B = 0.14, p = 0.506). Conclusions: Emotional and psychotic stress reactivity may be potential mechanisms linking childhood trauma with clinical outcomes in UHR individuals.